1988
DOI: 10.1128/aem.54.5.1277-1279.1988
|View full text |Cite
|
Sign up to set email alerts
|

Effects of some alkyl phenols on methanogenic degradation of phenol

Abstract: The effects of six phenolic compounds (o-, m-, and p-cresol and 2-, 3-, and 4-ethylphenol) on the anaerobic biodegradation of phenol was examined in batch methanogenic cultures. Results showed that ethylphenols were more inhibitory of phenol degradation than were cresols. The inhibitory effects of the three isomers of cresol and ethylphenol did not vary with the isomer but rather with the substituted functional group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…Th is relatively modest temperature decline would seem to be insuffi cient for the large increase in the concentrations of malodors. It is likely that a seasonal decline, related to shorter days or falling temperatures, in the populations of organisms such as photosynthetic bacteria (Wenke and Vogt, 1981) and/or methanogenic consortia (Wang et al, 1988;Gu and Berry, 1991) were at least partially responsible for increases in the concentrations of malodors. Do et al (2003), for instance, found that the population of photosynthetic purple nonsulfur bacteria peaked in the late summer to early fall and that Rhodobacter sp.…”
Section: Resultsmentioning
confidence: 99%
“…Th is relatively modest temperature decline would seem to be insuffi cient for the large increase in the concentrations of malodors. It is likely that a seasonal decline, related to shorter days or falling temperatures, in the populations of organisms such as photosynthetic bacteria (Wenke and Vogt, 1981) and/or methanogenic consortia (Wang et al, 1988;Gu and Berry, 1991) were at least partially responsible for increases in the concentrations of malodors. Do et al (2003), for instance, found that the population of photosynthetic purple nonsulfur bacteria peaked in the late summer to early fall and that Rhodobacter sp.…”
Section: Resultsmentioning
confidence: 99%
“…El hecho de que haya diferencias de producción de metano pueden atribuirse a la acumulación de ácidos grasos volátiles (AGV) en algunos digestores. Además, las bajas concentraciones (5 y 10 g SV) pueden ser insuficientes para activar la actividad de los microorganismos causando estrés microbiano, disminución del pH y fallas en los digestores [13]. No obstante, los resultados obtenidos de este trabajo han hecho que la producción de metano obtenida refleje valores similares a otros sustratos previamente reportados por Cuetos et al [14] y Bayr et al [15], donde la producción de metano varío entre 400 a 700 NmL de CH 4 /g SV, aunque las condiciones iniciales y parámetros de operación fueron diferentes.…”
Section: Potenciales De Metano De Los Residuos De Mataderounclassified
“…Bourgeois and Eisenhardt (1988) pointed out that the organization was changing its structure to adapt to this changing trend [3] . Pfeffer and Baron (1988) found that there was a clear interest link between structural change and organization [4][5] . This results in an obvious different form of governance of the traditional division and the market -the formation and formation of the form of network governance.…”
Section: Literature Reviewmentioning
confidence: 99%